2021
DOI: 10.16926/par.2021.09.18
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of physical education classes to daily physical activity levels of adolescents

Abstract: Introduction: Although practicing physical activity according to recommendations has health benefits, many studies have reported that the level of participation is lower than recommended. Methods: In this behavioural epidemiological study, we used a correlational design to determine the contribution made by physical education (PE) classes to daily physical activity in a sample of 694 Spanish adolescents. Physical activity levels were determined using the Four by One-Day Physical Activity Questionnaire. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…Results showed that the PE lesson exhibited the highest opportunity ratio values, thus representing the most opportune social occasion to engage all adolescents in MVPA. These data confirmed those reported by Sanz Martin et al (2021) and Gavarry et al (2003) who showed that, on the day the PE lesson took place, adolescents engaged in more MVPA [ 30 , 31 ]. However, its opportunity ratio level, between 23.6% (HEPA active profile) and 14.7 (inactive profile) was rather low and confirmed the systematic review of Burson et al (2021) showing that only 31% of the PE lesson is consecrated to MVPA [ 32 ].…”
Section: Discussionsupporting
confidence: 90%
“…Results showed that the PE lesson exhibited the highest opportunity ratio values, thus representing the most opportune social occasion to engage all adolescents in MVPA. These data confirmed those reported by Sanz Martin et al (2021) and Gavarry et al (2003) who showed that, on the day the PE lesson took place, adolescents engaged in more MVPA [ 30 , 31 ]. However, its opportunity ratio level, between 23.6% (HEPA active profile) and 14.7 (inactive profile) was rather low and confirmed the systematic review of Burson et al (2021) showing that only 31% of the PE lesson is consecrated to MVPA [ 32 ].…”
Section: Discussionsupporting
confidence: 90%
“…The results showed a significant difference between the percentage of adolescents who fulfilled physical activity on school days in Physical Education compared to non-Physical Education school days. Percentage of students meeting physical activity targets on school days in non-Physical Education classes (i.e., less than 50%), in line with other studies (Kalman et al, 2015;Sanz-Martín et al, 2021). Several studies have shown that learning physical education has a positive effect on the health of children and adolescents (Ardoy et al, 2014;Singerland et al, 2011).This certainly has a significant influence on the academic achievement of students in Physical Education.…”
Section: Discussionsupporting
confidence: 84%
“…Physical Education has a fundamental role in increasing students' daily physical activity (Sanz-Martín et al, 2021).From the results of research on junior high school students in the city of Padang, Indonesia, it turns out that students who have a level of physical fitness below the average are 53 people (53%) in the less and very less categories. Physical fitness is defined as the ability to do work efficiently, without causing significant fatigue (Gorski et al, 2019;Maslach & Leiter, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Students' psychological needs include independent needs, ability needs, and relationship needs; students' learning motivation includes self-efcacy, situational cognition, performance orientation, independent inquiry, and goal orientation; students' academic performance includes physical health performance and physical education academic performance [21]. Physical education teaching establishes a curriculum system, implements teaching organization, and conducts self-reference evaluation on students' learning achievements (including knowledge, ability, skills, and quality), so as to measure the training efect and the achievement of training objectives and form continuous improvement [22,23]. Tis requires that the professional structure of physical education teachers should also be updated, and the professional development mode must also be followed up.…”
Section: Analysis Of Teaching Mode Of Physical Educationmentioning
confidence: 99%